The role of technicians and technician institutions in rural development - Md Yassin, Sulaiman; M. Shaari, M. Ismail (1983)
The purpose of the paper is to submit for discussion the scope of rural development activities in Malaysia, the special roles played by technicians and technician institutions as well as to suggest measures for enhancing the role of technicians and technician institutions in rural development. The ideas posited in this brief country report constitute only an attempt by the writers to highlight the salient activities in Malaysian Rural Development and the issues relating to the role of technicians and technician institutions.